Analisis Pengaruh Corporate Social Responsibility Terhadap Kinerja Keuangan Perusahaan perusahaan Rokok yang Listing Pada Bursa Efek Indonesia Periode Tahun 2009-2011 - Wulan, Tirza Ana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Aims of this study was to examine CSR disclosure influence concerning financial performance within tobacco companies listed on Indonesian Stock Exchange. This research describes the influence of independent variable Corporate Social Responsibility disclosure on two dependent variables namely Return On Equity and stock return. This research included in the type of explanatory and population research. This research used 3 firms namely PT Gudang Garam Tbk., PT Hanjaya Mandala Sampoerna Tbk., and PT Bentoel Internasional Investama as a population for a period of 3 years from 2009- 2011. This research used linear regression to examine Corporate Social Responsibility disclosure effect to tobacco financial performance. The result couldn’t prove that both research hypothesis were Corporate Social Responsibility disclosure have positive influence to Return On Equity and stock return. It means that investors assess the Corporate Social Responsibility information disclosed by the companies in their annual reports for their investment decision. Keywords : Corporate Social Responsibility, Return On Equity, Stock Return